Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd003414.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Cycle regimens for frozen-thawed embryo transfer

Abstract: Cycle regimens for frozen-thawed embryo transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
1
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 54 publications
4
89
1
3
Order By: Relevance
“…The study revealed no significant advantage of any specific approach to prepare the endometrium for FET in terms of clinical pregnancy rates or live birth rates [75]. The results were in line with the previous systematic review published in 2008 [76]. Either way, and independently of the particular characteristics of segments B and C, there is no doubt that the segmentation approach for patients with OHSS works [70, 71, 77,78], and that the freeze-all policy in this situation is no longer controversial.…”
Section: Freeze-all For Whom?supporting
confidence: 89%
“…The study revealed no significant advantage of any specific approach to prepare the endometrium for FET in terms of clinical pregnancy rates or live birth rates [75]. The results were in line with the previous systematic review published in 2008 [76]. Either way, and independently of the particular characteristics of segments B and C, there is no doubt that the segmentation approach for patients with OHSS works [70, 71, 77,78], and that the freeze-all policy in this situation is no longer controversial.…”
Section: Freeze-all For Whom?supporting
confidence: 89%
“…Artificial cycles apply exogenous administration of estrogen and progesterone, and allow for a predictable monitoring of endometrial development and the advanced scheduling of embryo thaw and transfer. Some investigators have suggested that artificial cycles may optimize endometrial receptivity with a more consistent interval, duration, and concentration of estrogen and progesterone compared to the intrinsic variability of the LH surge, ovulation, and follicular/corpus luteum steroidogenesis of the natural cycle [Ghobara and Vandekerckhove 2008;Zheng et al 2013]. In addition, the introduction of GnRH agonist suppression to prevent spontaneous ovulation in artificial cycles [Dal Prato et al 2002;Gelbaya et al 2006;Hil et al 2010], has added a special type for artificial cycles.…”
Section: Introductionmentioning
confidence: 99%
“…В 2008 г. T. Ghobara и P. Vandekerckhove [44] про-вели анализ 7 рандомизированных контролируемых исследований, включивший 1120 женщин, которым перенос размороженных эмбрионов проводили в ЕЦ, на фоне ЗГТ (в том числе с десенситизацией ги-пофиза) и после стимуляции яичников. Авторы уста-новили, что вероятность родов живым плодом стати-стически значимо ниже в группе женщин, прини-мавших ЗГТ на фоне десенситизации гипофиза по сравнению с ЗГТ без десенситизации (OR 0,38, 95% CI 0,17-0,84; p=0,02).…”
Section: перенос размороженных эмбрионов на фоне згтunclassified